2015
DOI: 10.4172/2157-7617.1000309
|View full text |Cite
|
Sign up to set email alerts
|

Using Principle Component Analysis in Identifying Synoptic Patterns of Wet Periods in Central Iran

Abstract: Atmosphere circulation patterns have an important role in appearance of natural events. For this purpose, in the present study in order to identify the atmosphere circulation patterns which cause humid periods, the principle components analysis method and cluster analysis were used. Therefore by emphasis on peripheral circulation approach, wet periods during a 30 years statistic period in 6 synoptic stations in Kerman, Yazd and Isfahan province which have long term common statistic period were calculated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Effectual management of water resources is important due to the population growth and increasing problems of access to fresh water in arid and semiarid areas like Iran (Meidani et al,2014). In Iran, changes in precipitation caused by synoptic system (polar front, polar front jet stream, westerlies and etc..) and geographical factors (marine, continental, latitude, and elevation (height, lee slope and windward slope) (Barth & Steinkohl ,2004;Raziei et al,2013;Sabziparvar et al,2015).The synoptic patterns affecting Iran's rainfall also indicated that high pressure of Siberian and deep trough at the east of Mediterranean Sea and red sea, low pressure in Black sea and Monsoon are very important (Rasouli et al,2012;Fatemi at al.,2015,Delju et al,2013,Ahmadi et al,2019.…”
Section: Introductionmentioning
confidence: 99%
“…Effectual management of water resources is important due to the population growth and increasing problems of access to fresh water in arid and semiarid areas like Iran (Meidani et al,2014). In Iran, changes in precipitation caused by synoptic system (polar front, polar front jet stream, westerlies and etc..) and geographical factors (marine, continental, latitude, and elevation (height, lee slope and windward slope) (Barth & Steinkohl ,2004;Raziei et al,2013;Sabziparvar et al,2015).The synoptic patterns affecting Iran's rainfall also indicated that high pressure of Siberian and deep trough at the east of Mediterranean Sea and red sea, low pressure in Black sea and Monsoon are very important (Rasouli et al,2012;Fatemi at al.,2015,Delju et al,2013,Ahmadi et al,2019.…”
Section: Introductionmentioning
confidence: 99%